A bargain game theory assisted interest packet forwarding strategy for information centric network. (January 2023) - Dutta, Nitul
Abstract: In Information Centric Network (ICN), when implemented using NDN (Named Data Network) architecture, a client generates an 'interest' packet to retrieve a content. The interest packet carries the name of the searched content and may pull the data from any intermediate router that holds the requested content. An efficient interest packet forwarding mechanism is highly desirable in ICN to make the content retrieval faster. This paper describes an interest forwarding technique aiming at minimizing content retrieval time and network overhead. The process of interest forwarding is modelled as bargain game with data seeker as seller and content provider as buyer. Intermediate Content Routers (CRs) between the consumer and the actual producer is classified as either capable or incapable CRs represented as c CR and i CR respectively. Initially all CRs holds certain currency value based on their attributes. The c CRs are capable of serving interests and they are rewarded with a pre agreed trading price. The i CRs on the other hand are not capable of serving any content and hence they are rewarded by a fraction of the trading price based on the assistance provided in forming the data transmission path. To evaluate the strength of the new scheme the proposed bargain game theory (BGT) based technique is integrated with three existing protocols, namely, the Cache Less for More (CL4M), Characteristic Time Routing (CTR), and Probability based caching (pCache). The performance of new variations of these protocols are compared with their base versions. The simulation is performed in ns -3 based ndn Sim-2.0. Performance parameters observed in the simulation are, content search latency, server hit ratio, network load, overhead and throughput. Simulation observation reveals that the integration of the proposed scheme significantly improves the performance in terms of aforementioned parameters.